Multiculturalism in Islamic Reconstruction Theological Principles for Strengthening Religious Moderation - Miftahuljannah, Viona; Al Farabi, Mohammad; Darlis, Ahmad; Asmiralda, Febrina; Rahmah Puteri, Aulia; Mustafa Kareem, Yasir (Technomedia Journal, 2026)
The increasing complexity of cultural, religious, and identity diversity in the era of digital transformation poses significant challenges to social cohesion, driven by technology mediated communication, social media dynamics, and digital information flows that may intensify polarization, intolerance, and disinformation. This study examines multiculturalism from an Islamic perspective by analying its theological foundations, particularly the principles of ta’aruf, tasamuh, ‘adl, tawazun, rahmah, and shura, and by explaining the role of religious moderation (wasatiyyah) as an ethical framework for addressing social and digital challenges. Using a qualitative library research approach, data were collected from primary Islamic sources, including the Qur’an, Sunnah, and classical exegesis, as well as relevant contemporary literature, and analyzed thematically to identify conceptual patterns and interrelationships. The findings indicate that religious moderation plays a strategic role in strengthening social harmony and guiding ethical engagement in digital spaces, especially in response to social media communication, online religious discourse, and challenges related to algorithms and disinformation. The novelty of this study lies in integrating Islamic theological principles particularly wasatiyyah and ummatan wasathan with contemporary theories of strategic management and digital transformation, contributing to the development of multicultural education adaptive to digital society and supporting the achievement of the Sustainable Development Goals (SDGs), notably SDG 4, SDG 10, and SDG 16.